Mantras in the Erau Tradition in Kutai Kartanegara - Samsir, Samsir; Tang, Mahmud; Arifin, Ansar; Tahara, Tasrifin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
Traditions and mantras are essential elements in people's culture and life. This study focuses on mantras in the Erau tradition in Kutai Kartanegara Kingdom. Erau is one of Indonesia's cultural traditions, which is carried out annually with an activity center in Tenggarong, Kutai Kartanegara, East Kalimantan. In the Erau tradition, the mantras is vital in regulating society and determining social relations between citizens. It also acts as a source of inspiration and motivation for people to carry out their daily lives. This research was conducted to understand more about these mantras and how they are used in the context of the Erau tradition. This study also aims to discover the meanings of each mantra in the Erau tradition and how these mantras play a role in people's daily lives. The result of this study is that mantras is used as a local communication tool in the form of language, which has an essential role in seeding messages and culture. The characteristics of the mantra used are spoken language and the mention of all the supernatural beings believed to be the rulers of the supernatural realm. The meaning of the mantra is intended to seek permission from the rulers of the supernatural realm to hold the Erau event, to ensure the smooth conduct of the Kutai Kartanegara Erau activities, and to empower the king who leads his people simultaneously. The results of this study can be used as a reference in future studies on other traditions and mantras in different regions.